Distribution and risk factors of cleft lip and palate on patients from a sample of Damascus hospitals - A case-control study. Issue 9 (September 2021) - Nahas, Louei Darjazini; Alzamel, Omar; Dali, Mammdouh Yassin; Alsawah, Rama; Hamsho, Ahmad; Sulman, Rafi; Alzamel, Mohamad; Omar, Abdullah
Abstract: Objective: This case-control study was conducted to determine the distribution of cleft lip and/or palate, its association with family history, syndromes and serous otitis media (SOM), and its relation with several risk factors. Methods: The case group comprised of 133 children born with cleft lip and/or palate, and the control was 133 non-cleft children born full-term. Data was collected including age, gender, origin and risk factors for cleft lip and palate from patients' files, interviewing supervising doctors, and the patient. Data was then filled out into Excel and underwent statistical analysis using the Goodness of Fit Test and Chi-Square to determine the significance of the results. Results: Cleft lip and/or palate (CL/P) was slightly higher among males (51.9%). Combined cleft lip and palate (CLP) was the most common presentation (42.1%). Cleft lips (CL) were mostly complete cleft (51, 5%) incomplete cleft comprised (41.1%), In the sample 35.4% of the cases were bilateral, 32.3% were right unilateral, 28.3% were left unilateral and 4% were median cleft. Cleft palate (CP) was mostly complete (46.6%) there were incomplete clefts (40%), and the remainder were submucosal (13.4%). Isolated CL and combined CLP were higher in males (51.6%, 62.5% respectively). Both isolated CP and Tessier anomaly were more common in females (64.7% and 58.3% respectively). consanguineous marriages accounted for 36.1% of cases. 21.8% of the sample had a first-degree relative and 24.8% had a second degree relative born with CL/P. There were only 7 cases (0.05%) of syndromic CL/P: Down's (4), Pierre Robin's (2), and Van der Woude Syndrome (1). A relationship was found between CL/P and the risk factors: taking anticonvulsants (without specifying the drug) (p = 0.025, OR = 10.73 C.I. 95%), taking retinoic acid (p-value = 0.049, OR = 4.75 C.I. 95%), not consuming folic acid (p-value = 0.00, OR = 28.23 C.I. 95%), and smoking cigarettes (p-value = 0.046, OR = 2.00 C.I. 95%). There was no relationship with maternal alcohol consumption or maternal diabetes (p-values = 0.652 and 0.210, respectively). SOM was present in 63.2% of patients with CL/P and were mostly isolated CP. Conclusion: CL/P was only slightly higher among males. The most common condition was CLP. There was higher incidence of CL/P among second-degree relatives than first degree. Down's, Pierre Robin's, and Van der Woude Syndromes may be associated with CL/P. Taking anticonvulsants, taking retinoic acid, not consuming folic acid, and smoking cigarettes all have a role in the incidence of CL/P. More than half of the sample had an associated SOM. Abstract : Cleft lip, Cleft palate, Down's Syndrome, Van der Woude Syndrome, Pierre Robin's Syndrome, Syria.